Alternative core development around the tetracyclic indole class of HCV NS5A inhibitors. Issue 20 (15th October 2016) - Tong, Ling; Yu, Wensheng; Coburn, Craig A.; Meinke, Peter T.; Nair, Anilkumar G.; Dwyer, Michael P.; Chen, Lei; Selyutin, Oleg; Rosenblum, Stuart B.; Jiang, Yueheng; Fells, James; Hu, Bin; et al.
Graphical abstract: Abstract: Herein, we describe our research efforts to develop unique cores in molecules which function as HCV nonstructural protein 5A (NS5A) inhibitors. In particular, various fused tetracyclic cores were identified which showed genotype and mutant activities comparable to the indole-based tetracyclic core.